The misunderstood science of exercising on sunny days - Hutchinson, A. (2020)
To figure out how your body will respond in hot conditions, consider your "physiological equivalent temperature". Race directors and exercise physiologists don`t just look at a thermometer (or even the Heat Index, which factors in humidity but not solar radiation or wind) to guess how runners are going to fare on hot days. Instead, the scale of choice is the "wet-bulb globe temperature," or WBGT, which combines measurements from three types of thermometer: an ordinary dry bulb to measure air temperature, a wet bulb that incorporates the effects of humidity and wind, and a globe thermometer that measures solar radiation. WBGT is simply a weighted average of the three measurements, based 70 percent on the wet-bulb reading, 20 percent on the globe, and 10 percent on the dry-bulb. argues that Now. a new study argues we can do better with a different scale called the Physiological Equivalent Temperature, or PET, which predicts risk more effectively, especially on sunny days ...